The Carit Maneuver: A Novel Approach for the Relief of Shoulder Dystocia—A Case Series - Gei, Alfredo F; Mastache, Jorge Suarez; Pacheco, Luis D.; Villanueva, Mariana (American Journal of Perinatology Reports, 2020)
Objective The main purpose of this article is to describe the technique and mechanism of action of a novel intervention for the relief of shoulder dystocia we are labeling Carit maneuver.Methods We report a cohort study of eight cases of shoulder dystocia not relieved by the combination of McRobert's maneuver and suprapubic pressure treated with the Carit maneuver. This intervention involves the use of the fetal head and neck as the grasping point of the fetus to exert a ventral rotation of the fetal trunk, reduce the bi-acromial diameter, and deliver the posterior shoulder by passive displacement.In all these cases, the direction of the original head restitution, direction of exerted rotation, and side and location of delivery of the first shoulder were recorded. Maternal and neonatal outcomes were reviewed and reported.Results In all cases, the Carit rotational maneuver resulted in the delivery of the posterior shoulder in the transverse (4), oblique anterior (2), or direct anterior (2) diameters. No instances of neonatal depression or fetal acidemia were noted in this cohort.Conclusion The Carit maneuver is an original and successful intervention in the management of shoulder dystocia unresponsive to McRobert's maneuver and suprapubic pressure.
Keywords: shoulder dystocia; shoulder girdle dystocia; rotational maneuver; Carit maneuver